Pengaruh Lama Penyimpanan Adonan Pada Metode Autolisis Dalam Pembuatan Donat Terhadap Daya Terima Konsumen - Farhansyah Muhammadien; Guspri Devi Artanti; Cucu Cahyana (Universitas Negeri Medan, 2021)
This study aims to analyze the effect of dough storage time on the autolysis method in making donuts on consumer acceptance. This study used an experimental method with the treatment of differences in storage time for dough with autolysis methods in making donuts with different lengths of time, namely 40 minutes, 60 minutes, and 80 minutes. Organoleptic analysis was carried out using a hedonic quality test on volume, skin color, frying average, shape, skin character, pores, aroma, crumb color, taste, tissue texture, quality of chewing, and oil absorption rate with 5 aspects of a rating scale and carried out by 3 trained panelists. Based on the results of the long test of dough storage on the autolysis method in making donuts, it has the highest average volume aspect, namely 4.3 with a large scale rating. The assessment of the skin color aspect has the highest average value, namely 4.7 with a brownish yellow rating scale. The assessment of the average aspect of the frying pan has the highest average value, namely 4.3 with an average rating scale. The shape aspect assessment has the highest average value, namely 4.3 with a round rating scale, the hole is in the middle of a small circle. Assessment of skin character aspects has the highest average value, namely 4.3 with a soft rating scale. The assessment of the pores aspect has the highest average value, namely 4.3 with a small rating scale. The results of donuts made using the autolysis method showed that the results of the hypothesis test were statistically significant and not significantly different (α = 0.05). Statistically, the organoleptic test results at an error rate of 0.05 did not show significantly different results in the aspects of shape, volume, skin color, aroma, crumb color, pores, tenderness, and chewing quality of donuts made using the autolysis method.